Measuring Attitudes Toward Sponsor And Purchase Intention - Dinh Toan Nguyen; Huy Thong Vu (Cogent Business & Management, 2022)
This study was conducted to investigate the impact of exposure to sponsored events, involvement with sponsored events, and sponsor-event congruence on attitudes toward sponsor and purchase intention. The paper first reviews existing literature and then develops related hypotheses to achieve its objectives. The study combined both qualitative and quantitative research methods. It was conducted by surveying 293 participants and followers of the Vietnamese Rap 2020-an event sponsored by Pepsico. Structural equation modeling (SEM) was used to test the proposed hypotheses. The research results indicated that exposure to sponsored events, involvement with sponsored events, and sponsor-event congruence had a significantly positive effect on attitudes toward sponsor. Furthermore, involvement with a sponsored event, sponsor-event congruence, and attitudes toward sponsor had a positive effect on purchase intention. Based on the study's empirical findings, some suggestions are provided to help enterprises improve the effectiveness of sponsorship activities.
Keywords: 650; attitude toward sponsor; Exposure to sponsored event; involvement with sponsored event; purchase intention; sponsor-event congruence